Mechanisms of octanoic acid potentiation of insulin secretion in isolated islets. Issue 4 (4th July 2019) - Zhang, Tingting; Chen, Pan; Stanley, Charles A.; Hoshi, Toshinori; Li, Changhong
ABSTRACT: A potentiating effect of medium-chain triglycerides on glucose-stimulated insulin secretion (GSIS) has been observed since the 1960s. Subsequent observations identified octanoic acid (OA), the main component of medium-chain triglyceride, as the potentiator of GSIS, but the mechanism was unclear. We used wild-type (WT), short-chain 3-hydroxyacyl-CoA dehydrogenase knockout ( Hadh - /- ), and sulfonylurea receptor 1 knockout ( Sur1 - /- ) mouse islets to define the mechanism of OA potentiation of insulin secretion. Application of OA alone induced a 2- to 3- fold increase of insulin secretion with an apparent threshold of 3 mM in WT mouse islets, suggesting that OA itself is a weak insulin secretagogue. However, OA at 1 mM strongly potentiated fuel-stimulated insulin secretion, especially GSIS. The potentiating effect on fuel-stimulated insulin secretion by OA did not require fatty acid β-oxidation because OA also potentiated amino acid-stimulated insulin secretion in islets isolated from Hadh - /- mice, which cannot fully oxidize OA. Measurements using Sur1 - /- islets indicated that the potentiating effect of OA on fuel-stimulated insulin secretion is Ca 2+ dependent and is often accompanied by β-cell membrane potential depolarization, and may also involve the Ca 2+ /calmodulin complex. Experiments using DCPIB, an ethacrynic acid derivative, to inhibit volume-sensitive anion channels (VSACs) in Sur1 - /- islets demonstrated that the potentiation effects of OA on insulin secretion are in part medicated by activation of VSAC. In addition, inhibition of IP3 receptor also abolishes the OA-induced intracellular Ca 2+ increase in Sur1 - /- islets.